2015
DOI: 10.1038/ncomms9945
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immunity increases the pace and predictability of evolutionary change in commensal gut bacteria

Abstract: Co-evolution between the mammalian immune system and the gut microbiota is believed to have shaped the microbiota's astonishing diversity. Here we test the corollary hypothesis that the adaptive immune system, directly or indirectly, influences the evolution of commensal species. We compare the evolution of Escherichia coli upon colonization of the gut of wild-type and Rag2−/− mice, which lack lymphocytes. We show that bacterial adaptation is slower in immune-compromised animals, a phenomenon explained by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 48 publications
(85 reference statements)
10
104
1
Order By: Relevance
“…We note that despite the allelic variation within each target of adaptation, only one allele representative of each locus was tested. While for the gat locus we have previously shown that different alleles have equivalent selective effects [8,27], we acknowledge that for the second targets of adaptation, different alleles may have different phenotypes.…”
Section: Resultsmentioning
confidence: 97%
“…We note that despite the allelic variation within each target of adaptation, only one allele representative of each locus was tested. While for the gat locus we have previously shown that different alleles have equivalent selective effects [8,27], we acknowledge that for the second targets of adaptation, different alleles may have different phenotypes.…”
Section: Resultsmentioning
confidence: 97%
“…Genotype discrimination can be limited by an inability to detect a beneficial strain that evolves a pathogenic phenotype, or vice versa. The adaptive immune system can solve this problem by learning new associations during infection—combining trait and genotypic information—and adaptive immunity can impact the microbiota 49,51 . However, it is not yet clear whether this results in effective control of the microbiota at epithelial surfaces.…”
Section: Host To Microbe: the Importance Of Host Controlmentioning
confidence: 99%
“…We, therefore, expect natural selection to favour hosts that act as ecosystem engineers that influence not only individual species but also community-level properties, such as stability and productivity 14 . Possible mechanisms of this control include the immune system 49 and epithelial mucus secretion, which can weaken ecological interactions by regulating species density and increasing spatial structure 14 . Interrupting the immune system or mucus secretion 22,52 , therefore, may lead to a less stable, and thus less diverse, microbiota.…”
Section: An Ecosystem On a Leashmentioning
confidence: 99%
“…However, not only do animals tolerate a complex microbiome, in the case of B. fragilis provoking an immune response paradoxically enables intimate association with its mammalian host. Related commensal bacteria may also benefit from actively engaging IgA during symbiosis, as Rag2 −/− mice devoid of adaptive immunity harbor fewer Bacteroides (43), and both B cell deficient and IgA −/− animals display decreased colonization by the Bacteroidaceae family (44). IgA has been previously shown to increase adherence of Escherichia coli (15), Bifidobacterium lactis, and Lactobacillus ramnosus (16) to tissue-cultured epithelial cells, suggesting that these microorganisms may also benefit from IgA to establish a mucosal bacterial community.…”
Section: Main Textmentioning
confidence: 99%